Notarial Liability in Apartment Pre-Sale and Purchase Agreements: Consumer Protection and Legal Certainty - Desyanti Desyanti; Hanif Nur Widhiyanti; Amelia Sri Kusuma Dewi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
Apartment Sale and Purchase Binding Agreements (PPJB) drafted by notaries are frequently executed without satisfying the prerequisites stipulated under Article 43 of Law No. 20 of 2011 on Flats (Apartment Law), which requires certainty of land status, Building Construction Permit (IMB), infrastructure availability, and a minimum construction completion of 20% prior to marketing. This normative juridical research analyses legal certainty and consumer protection in the execution of apartment PPJBs drafted by notaries, employing statutory, conceptual, and case approaches. The study finds that notaries bear an implicit obligation to verify the fulfilment of legal prerequisites as a consequence of the due diligence principle enshrined in Article 16 paragraph (1) letter (a) of the Notary Profession Law (UUJN). Notarial negligence gives rise to civil, administrative, criminal, and moral-ethical liability. Furthermore, the existing consumer protection legal framework does not provide adequate substantive protection owing to weak supervision, deficient sanction enforcement, and inadequate recovery mechanisms. The study recommends a comprehensive legal reconstruction encompassing: the establishment of a marketability certification system, explicit affirmation of notarial verification obligations within the UUJN, strengthened sanctions for developers, the creation of a consumer protection guarantee fund for the property sector, and enhanced institutional capacity of the Consumer Dispute Settlement Agency (BPSK) and courts in handling property consumer disputes.